Eucalyptus globulus essential oil on the postharvest quality of ‘Carola’ roses - Almeida, Elka Fabiana Aparecida; Santos, Leandra Oliveira; Castricini, Ariane; Reis, João Batista Ribeiro da Silva (Ornamental Horticulture, 2020)
The consumer market has been demanding quality plant products, without any contamination or chemical residues, restricting their use in postharvest. As a result, is necessary increase the development of research seeking more sustainable and economic alternatives. The objective was to identify the ideal concentration of eucalyptus essential oil to maintain postharvest quality of ‘Carola’ roses. At laboratory, stems of the ‘Carola’ roses were standardized at 35 cm, labeled and subjected to the following doses of eucalyptus (Eucalyptus globulus) essential oil: 0.25%; 0.5%; 0.75%; 1.0% and 1.25%. Spraying with distilled water was used as a control. The experiment was conducted in a completely randomized design, in a factorial scheme consisting of two factors: six postharvest treatments and seven evaluation dates (0, 1, 2, 3, 4, 5, 6 and 7 days). Four replications were used, with two flowers each. Stems fresh mass and color of the petals were analyzed daily. In addition, the visual quality was also evaluated. The total anthocyanin content in the petals was evaluated every three days at the beginning, middle and end of the experimental period. Eucalyptus essential oil in all doses tested provided better maintenance on the postharvest quality of roses: 0.25% and 0.5% (better grades), 1.0% and 1.25% (lower hue angle) and 0.25% (higher anthocyanin content). On the 5th day, the flower stems lost 16% of fresh mass, without signs of wilting and the assigned scores also indicated that the stems remained fit for commercialization until the fifth day (total vase life). In conclusion, eucalyptus essential oil at doses 0.25%, 0.50%, 1.0% and 1.25% is effective in maintaining the quality of ‘Carola’ roses for up to five days at 25 °C.